Correlation Between Neutrophil to Lymphocyte Ratio (NLR) and Patient with Heart Failure: Haematology Variables in Patient with Heart Failure - Fransiskus Xaverius Rinaldi; Stefanus Lembar; Denio Adrianus Ridjab; Leonardo Leonardo; Jessica Lauryn; Erlina Erlina; Gregiorio Gavriel Singgih (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Heart failure is a condition of the heart that cannot pump blood adequately resulting in systemic tissue hypoperfusion. This situation will cause systemic inflammatory reactions. Neutrophil to Lymphocyte Ratio (NLR) is an inexpensive and easy parameter that can see inflammatory reactions. This research uses descriptive and analytical studies with cross-sectional studies. The number of samples was 67 heart failure patients who were treated at Atma Jaya Hospital. The statistical test used is unpaired T-test to see if there was a correlation between the NLR value in heart failure, after that NLR cut-off point will be analyzed using a receiver operating curve (ROC). Pearson correlation test was conducted to see the correlation of NLR with laboratory results, including haemoglobin, hematocrit, leukocytes, and platelet. The results showed a significant difference of NLR between controls and heart failure patients (p = 1.0402-10). The cut-off point is 2.16 with an area under the curve of 86.4%, sensitivity 79.1%, and specificity 91%. Analysis of NLR data on heart failure with hemoglobin (p = 0.108), hematocrit (p = 0.091), and platelets (p = 0.832) showed no significant correlation, whereas showed a significant correlation with leukocytes (p = 0.017). This study shows a significant difference of NLR between control and heart failure therefore it can be used to predict the prognosis for heart failure. This study also found no significant correlation between NLR with the amount of haemoglobin, hematocrit, and platelets, while there was a correlation with leukocytes.